Managing very large IT projects in businesses and organizations - Guah, Matthew W., 1963- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
"This book offers authoritative research on the fundamental theory, practice, and implementation of very large successful IT projects in organizations"--Provided by publisher.